2018
DOI: 10.1186/s13075-018-1525-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 family cytokines and soluble receptors in systemic lupus erythematosus

Abstract: BackgroundDysregulated production of cytokines has a critical role in systemic lupus. The aim of this work is to identify, by a comprehensive analysis of IL-1 family cytokines and receptors in serum, correlation between cytokines/receptors’ levels and the clinical and serological features of the disease.MethodsA full clinical evaluation was performed in 74 patients with systemic lupus erythematosus (SLE). C3, C4, anti-dsDNA and anti-C1q antibodies were measured. Cytokines of the IL-1 family (IL-1α, IL-1β, IL-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 46 publications
5
35
3
5
Order By: Relevance
“…Results for ALS, SLE, and IgG4-related disease (RD) are from references [28, 29, 3133] n.t. not tested…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results for ALS, SLE, and IgG4-related disease (RD) are from references [28, 29, 3133] n.t. not tested…”
Section: Discussionmentioning
confidence: 99%
“…Measurable concentrations of IL-18 are detectable in sera of normal subjects, yet are increased in many pathological conditions [26, 27]. In pathological conditions in which both IL-18 and IL-18BP were measured, such as amyotrophic lateral sclerosis (ALS), systemic lupus erythematosus (SLE), and IgG4-related disease, the higher levels of circulating IL-18 are paralleled by increased circulating IL-18BP, most likely as an attempt to counteract the excess of IL-18 [2833]. Similar to IL-1, IL-18 in AD appears to be a sign of increased inflammation, with higher levels of circulating IL-18 in AD patients, accumulation of IL-18 mRNA and protein in the AD brain and CSF, and increased production of IL-18 by AD monocytes [3436].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, monocytes play a fundamental role in the production of proinflammatory cytokines present in the peritoneal cavity and plasma from SLE-induced mice [54]. IFN-γ and TNFα [28] contribute to the great influx of CD4 T cells towards the peritoneal cavity in the first months after induction [55], whereas IL-1 has been considered a biomarker of disease activity or organ involvement in humans [56] [57].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our model, the percentage of Treg cells in the blood was negatively correlated with TNFα and positively correlated with TGF β1 ; no correlation between Treg cells and IL-2 and IL-10 was observed. Thus, higher titers of TNFα [57] may play an important role in SLE development and could be responsible for an increased proinflammatory response especially in active disease [57] [75]. TGF β1 promotes the development of peripheral Treg cells, and curiously, IL-2, produced by activated T cells [72], may regulate Treg proliferation that contributes to homeostasis and maintenance of Treg suppressive capacity [65], which suggests a negative feedback.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, at least two studies reported different results. Italiani et al [29] conducted a study on IL-1 family molecules and SLE, and reported that IL-33 was significantly lower in SLE ( p = 0.002), whereas soluble interleukin 1 receptor 4 (sIL-1R4), its natural inhibitor, was significantly higher ( p < 0.0001). Moreover, they found no correlation between proteinuria and IL-33.…”
Section: Autoimmune Disordersmentioning
confidence: 99%